Daptomycin Resistance Occurs Predominantly in vanA-Type Vancomycin-Resistant Enterococcus faecium in Australasia and Is Associated With Heterogeneous and Novel Mutations - Li, Lucy; Higgs, Charlie; Turner, Adrianna M.; Nong, Yi; Gorrie, Claire L.; Sherry, Norelle L.; Dyet, Kristin H.; Seemann, Torsten; Williamson, Deborah A.; Stinear, Timothy P.; Howden, Benjamin P.; Carter, Glen P. (Frontiers in Microbiology, 2021)
Healthcare associated infections caused by vancomycin-resistant Enterococcus faecium (VREfm) have a major impact on health outcomes. VREfm is difficult to treat because of intrinsic and acquired resistance to many clinically used antimicrobials, with daptomycin being one of the few last line therapeutic options for treating multidrug-resistant VREfm. The emergence of daptomycin-resistant VREfm is therefore of serious clinical concern. Despite this, the impact that daptomycin-resistant VREfm have on patient health outcomes is not clearly defined and knowledge on the mechanisms and genetic signatures linked with daptomycin resistance in VREfm remains incomplete. To address these knowledge gaps, phenotypic daptomycin susceptibility testing was undertaken on 324 E. faecium isolates from Australia and New Zealand. Approximately 15% of study isolates were phenotypically resistant to daptomycin. Whole genome sequencing revealed a strong association between vanA-VREfm and daptomycin resistance, with 95% of daptomycin-resistant study isolates harbouring vanA. Genomic analyses showed that daptomycin-resistant VREfm isolates were polyclonal and carried several previously characterised mutations in the liaR and liaS genes as well as several novel mutations within the rpoB, rpoC and dltC genes. Overall, 70% of daptomycin-resistant study isolates were found to carry mutations with the liaR, rpoB, rpoC or dltC genes. Finally, in a mouse model of VREfm bacteraemia, infection with the locally-dominant daptomycin-resistant clone led to reduced daptomycin treatment efficacy in comparison to daptomycin-susceptible E. faecium. These findings have important implications for ongoing VREfm surveillance activities and the treatment of VREfm infections.